Perlindungan Konsumen Terhadap Klausul Baku Yang Merugikan Pada Layanan Pinjaman Online Berbasis Aplikasi - Ramlin Ahmad; Renytha Mariana Hengkenang; Maura Amanda Putri (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
The rapid development of online loan (Pinjol) services in Indonesia has been accompanied by widespread use of detrimental standard clauses in consumer agreements. This normative legal research aims to (1) identify the forms of unfair standard clauses in online loan agreements, (2) analyze their legal compliance with Law Number 8 of 1999 concerning Consumer Protection (UUPK) and OJK Regulation Number 30 of 2024, and (3) formulate effective legal protection and dispute resolution for consumers. The results show that exoneration clauses and liability transfer clauses to third parties (e.g., debt collectors) are the most common forms of detrimental clauses. These clauses violate Article 18 of the UUPK and the principle of good faith in contracts, making them void by law. The study concludes that there is a significant gap between the legal framework and its implementation. A comprehensive approach is needed, including strengthening ex-ante supervision by OJK, standardizing contracts, empowering vulnerable. consumers, and creating integrated, accessible dispute resolution mechanisms to build a fair and transparent digital lending ecosystem.